ANALISIS YURIDIS TINDAKAN DISKRESI KEPOLISIAN PADA TAHAP PENYIDIKAN - Manalu, Sahata (Universitas Katolik Santo Thomas Medan, 2020)
In carrying out its professional duties, the National Police has the authority of discretion that can be carried out in certain circumstances. Discretion is an authority given by law to law enforcement officers, especially the police to act in special situations in accordance with the judgment and conscience of the agency or the officer himself. This research formula is: 1). How to implement police discretion at the investigation stage; and 2). How far the effectiveness of the implementation of police discretion at the investigation stage. This research is a normative legal research, which uses secondary legal material as the main data. From the results of this study concluded that 1) The use of police discretion in stopping investigations, it appears that there is authority in certain cases or circumstances to make a decision whether to take action or not if a crime occurs and there are factors that influence the discretion of the police in stopping investigations between Other legal factors; law enforcement factors; community factors; infrastructure factors; and legal cultural factors; 2. The effective implementation of discretion must be carried out with caution by improving the quality of human resources in the field of law enforcement as well as the power or authority that is carried out based on law based on considerations and beliefs and emphasizes more on moral considerations rather than legal considerations and provides real justice by paying attention the risk and benefit side of an action taken